Perceptions of hyperbaric oxygen therapy among podiatrists practicing in high‐risk foot clinics - Henshaw, Frances R (Int Wound J, 2018)
Foot ulceration is a devastating and costly consequence of diabetes. Hyperbaric oxygen therapy is recognised as an adjunctive therapy to treat diabetes‐related foot ulceration, yet uptake is low. Semi‐structured interviews were conducted with 16 podiatrists who manage patients with foot ulcers related to diabetes to explore their perceptions of, and the barriers/facilitators to, referral for hyperbaric oxygen. Podiatrists cited logistical issues such as location of facilities as well as poor communication pathways, lack of delegation and lack of follow up when patients presented for hyperbaric treatment. In general, podiatrists had an understanding of the premise of hyperbaric oxygen therapy and evidence to support its use but could only provide very limited citations of key papers and guidelines to support their position. Podiatrists stated that they felt a patient was lost from their care when referred for hyperbaric oxygen and that aftercare might not be adequate. Improved referral and delegation pathways for patients presenting for hyperbaric oxygen, as well as the provision of easily accessible evidence to support this therapy, could help to increase podiatrists’ confidence in deciding whether or not to recommend their patients for hyperbaric oxygen therapy.